Mucogingival surgery in the interdisciplinary management of patients with palato-alveolar cleft defects - Francina Maria Escobar Arregocés (Wolters Kluwer Medknow Publications, 2020)
Here will present a mucogingival technique for interdisciplinary management in patients with palato-alveolar cleft defect sequelae. Mucogingival continuity is sought in these patients by means of an extended laterally positioned flap. Achieving a mucogingival seal in the cleft area would be of great value in interdisciplinary management, favoring the prognosis of subsequent treatments, such as alveolar bone grafts, orthodontics, and rehabilitation, to achieve more esthetic and functional and harmonious results for the patients' dentogingival complex.